Enantioselective carbene insertion into the N–H bond of benzophenone imine - Yang, Jian (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Efficient enantioselective insertion of α-diazoesters into the N–H bond of N-sp(2)-hybridized benzophenone imine was realized by using Rh(2)(esp)(2) and chiral guanidine cooperative catalysis. Both aliphatic and aromatic substituted α-amino esters were obtained in high yields (up to 99%) and good enantioselectivities (up to 95.5 : 4.5 er) under mild reaction conditions.